ANALISISISTEM AKUNTANSI PENJUALAN KREDIT PADA KOPERASI KERTA RAHARJA - Zulkarnain Moeshak Zen; Endi Pratama (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2018)
A cooperative society found over and above to look for as big as profit it and for mensejaterakan members its and keeps its effort viability. Indeed this effort directness gets to materialize if goods that is on the market get to be accepted at marketing,and gets to pull market compartment. Therefore, essential for a cooperative society study sell system, since sell constitutes resource for a cooperative society. One of the ways that is utilized to increase sell is by use of credit sell system. To reach to the effect that, chairman of co-op needs a system for can help to arrange internal control who can give information in as much as which co-op progress already been reached, and gets mempertanggungjawabkan co-op wealth that is turned over on it. On a basic condition upon is seen needs to know sell system implement credit on a cooperative society KertaRaharja. This research intent to know sell accounting system implement credit on A Cooperative Society Kerta Raharja. What is credit Sell Accounting System on A Cooperative Society Kerta Raharja has accomplished Internal Control System that is equal to. Observational method that is utilized is analisis's method descriptive. Observational result that doing to point out that credit sell accounting system on A Cooperative Society Kerta Raharja was passably but still needful to been done sell transactions registry into sell and ledger journal.